2022
DOI: 10.1021/acs.biochem.2c00157
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mechanisms for DNA Engagement by BET Bromodomain-Containing Proteins

Abstract: Epigenetic reader domains regulate chromatin structure and modulate gene expression through the recognition of post-translational modifications on histones. Recently, reader domains have also been found to harbor double-stranded (ds) DNA-binding activity, which is as functionally critical as histone association. Here, we explore the dsDNA recognition of the N-terminal bromodomain of the bromodomain and extra-terminal (BET) protein, BRD4. Using protein-observed 19F NMR, 1H-15N HSQC NMR, electrophoretic mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…The majority align along a face of the alpha helical bundle and are comprised of a charged patch rich in arginine and lysine, whereas recently BRD4 BD2 was shown to bind DNA using a pocket largely overlapping with the acetyl-lysine binding pocket. In addition, adjacent motifs such as the AT-hooks and intrinsically disordered linkers can contribute to the DNA binding ( 51 , 62 , 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority align along a face of the alpha helical bundle and are comprised of a charged patch rich in arginine and lysine, whereas recently BRD4 BD2 was shown to bind DNA using a pocket largely overlapping with the acetyl-lysine binding pocket. In addition, adjacent motifs such as the AT-hooks and intrinsically disordered linkers can contribute to the DNA binding ( 51 , 62 , 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BRD3 and BRD4 BDs associate with non-coding RNA (ncRNA) ( 49 , 50 ). The binding of BDs to DNA has largely been found not to enhance affinity for histone peptides, though interestingly it was recently found that for BRD4 BD2 binding to DNA blocked histone peptide binding ( 51 ). However, for the BRD4 BD1–BD2 cassette, RNA binding was found to enhance association with acetylated histone tails ( 47 ), though the mechanism for this is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nucleosomal H4 tail accessibility is reader-dependent (also recently demonstrated for PHIP BD1-BD2 Morgan et al, 2021 ), and the ability to bind may rely on several factors including overall affinity or different engagement mechanisms. For instance, BRD4 BD1 (unlike BPTF BD) can associate with DNA ( Miller et al, 2016 ; Kalra et al, 2022 ), and such competition may help disengage the H4 tail from the nucleosome core.…”
Section: Resultsmentioning
confidence: 99%
“…The 19 F chemical shift is hyper-responsive to different chemical environments 41 and because of the small van der Waals radius, 19 F incorporation is generally biocompatible and structural nonperturbing 42 , 43 . As a result, an extrinsic 19 F label of fluorinated Trp allows the quantification of the Trp conformation distributions free of the protein background NMR signals 44 50 . We first carried out NMR experiments on 5-fluorotryptophan (5FW) substituted wild type (WT) BLUF domain in AppA, Sy PixD and Oa PAC, since 5FW is the most frequently used as a 19 F NMR probe among all fluorinated Trp amino acids 41 .…”
Section: Resultsmentioning
confidence: 99%